2019
DOI: 10.1186/s13072-019-0254-0
|View full text |Cite
|
Sign up to set email alerts
|

Preconception paternal alcohol exposure exerts sex-specific effects on offspring growth and long-term metabolic programming

Abstract: BackgroundAlthough clinical data support an association between paternal alcohol use and deficits in child neurocognitive development, the relationship between paternal drinking and alcohol-induced growth phenotypes remains challenging to define. Using an established mouse model of chronic exposure, previous work by our group has linked preconception paternal alcohol use to sex-specific patterns of fetal growth restriction and placental dysfunction. The aim of the present study was to investigate the long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 135 publications
(125 reference statements)
6
71
1
Order By: Relevance
“…In rodents, chronic paternal alcohol use affected insulin signaling and lipid homeostasis in the offspring through paternally inherited alterations in liver × receptor activity ( Chang et al, 2019a ). Similar findings were reported by Chang et al (2019b) , assessing long-term impacts of chronic preconception paternal alcohol use in mice. Evidence of metabolic programming in offspring included suppressed cytokine profiles within the liver and pancreas, consistent with findings from this study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In rodents, chronic paternal alcohol use affected insulin signaling and lipid homeostasis in the offspring through paternally inherited alterations in liver × receptor activity ( Chang et al, 2019a ). Similar findings were reported by Chang et al (2019b) , assessing long-term impacts of chronic preconception paternal alcohol use in mice. Evidence of metabolic programming in offspring included suppressed cytokine profiles within the liver and pancreas, consistent with findings from this study.…”
Section: Discussionsupporting
confidence: 86%
“…Also, due to ethical concerns, we were only able to include a limited number of rats per group, thus, only male offspring were examined. However, there are sex-specific effects on offspring growth and long-term metabolic programming ( Chang et al, 2019b ), thus, comparable studies on female offspring are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been over 40 published paternal preconception alcohol exposure studies in rodents (for review, see Finegersh et al., ), most varying in species, route of administration, and duration. Despite these differences, some intergenerational (F1) effects have been consistent such as low fetal and birthweight (Bielawski et al., ; Chang et al., , ; Ledig et al., ), altered organ weights (Abel, ; Chang et al., ; Ledig et al., ; Lee et al., ), and increased number of runts (Bielawski and Abel, ; Bielawski et al., ). Additional phenotypes reported include increased cortical thickness (Jamerson et al., ), reduced testosterone (Abel and Lee, ), and altered neurotransmitter levels (Nelson et al., ).…”
Section: Heritability Of Preconception Alcohol Exposurementioning
confidence: 99%
“…Remarkably, rodent studies have demonstrated that paternal preconception ethanol (PPE) exposure leads to molecular, cellular, physiological, and behavioral abnormalities in offspring (for reviews, see: [ 11 , 12 ]). For example, PPE-sired offspring exhibited insulin hypersensitivity and upregulated transforming growth factor beta signaling [ 13 ], altered enzymes and proteins involved in metabolism and weight gain [ 14 ], and altered levels of neurotrophins like brain-derived neurotrophic factor and nerve growth factor [ 15 , 16 ]. Paternal alcohol consumption impaired spatial learning performance in the eight-arm radial maze in male offspring while there was no change observed in an object exploration/recognition task compared to controls [ 17 ].…”
Section: Introductionmentioning
confidence: 99%